New Uzbekistan and Human Rights - Khatamov Farkhod Fahritdinovich (Peerian Journals Publishing, 2022)
This article scientifically analyzes the principle of "Respect for human rights in the New Uzbekistan" based on the reforms adopted at the initiative of President Shavkat Mirziyoyev. The practical significance of the concept of human rights in the process of formation of democratic values, civil society and free market relations in our country is revealed.
Keywords: Human rights; democracy; reform; New Uzbekistan